Minimizing Alkali Usage Through Ultrasound Treatment of Oil palm Empty fruit Bunch (OPEFB) Fiber Reinforced Poly(Lactic) Acid Composites - Akindoyo, John Olabode; Beg, M. D. H.; Suriati, Ghazali; M. R., Islam (2014)
Removal of the non-cellulosic components of natural fibers with minimum damage to the fibers had been one of the challenges to natural fiber reinforced polymer composites. Alkali treatment had been one of the very efficient means of fiber treament. However, environmental concerns make it expedient to always reduce the concentration of alkali for any fiber treatment as mush as possible. In this study, ultrasonic treatment in an alkali medium of low concentration was used to modify the surface of oil palm empty fruit bunch (OPEFB) fibers. Surface morphology of fibers due to treatment was studied by scanning electron microscopy (SEM) while its structural changes were studied by Fourier transforms infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Composite were prepared from oil palm empty fruit bunch fiber and poly(lactic) acid(PLA) through extrusion followed by injection moulding. Composite characterization was done by mechanical testing such as tensile, flexural and impact, structural analysis was done by XRD and thermogravimetric analysis (TGA) was also to investigate composite thermal stability. Result showed that the treatment of OPEFB fibers with ultrasound produced composites with highly desirable properties.